Models of teaching connecting student learning with standards - Dell'Olio, Jeanine M.; Donk, Tony.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2007)
'Models of Teaching' presents models of teaching as they relate to content standards and benchmarks and the creative process of original curriculum development. These topics are treated in both conceptual and practical ways.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Teaching -- Standards; Effective teaching; Teaching -- Methodology; Electronic books